2022
DOI: 10.3390/horticulturae8040278
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Oolong Tea Products in Different Regions and the Contribution of Thirteen Phytochemical Components to Its Taste

Abstract: Regionality is a term used in the tea industry to describe the particular style of tea produced by a growing region. Determining the characteristics of the tea of specific regions can help growers predict tea plant quality before harvesting and eventually production. As such, in this study, we collected representative Oolong tea samples from 15 regions in 8 countries. Quantitative description analysis (QDA) and a flavor wheel were used to analyze their sensory characteristics. Chemometrics was used to screen t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…Flavonoids belong to phenols, which are mainly bitter and astringent, while free amino acids are mainly umami and sweet [ 10 ]. Therefore, within a moderate range, a low content of flavonoids and other phenolic compounds and a high content of free amino acids in tea tender shoots are the material basis for making high-quality tea [ 14 ]. According to the results of the biochemical components analysis and total metabolic spectrum, GC-40 was found to still have the material basis for making high-quality tea because the contents of flavonoids and free amino acids were upregulated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids belong to phenols, which are mainly bitter and astringent, while free amino acids are mainly umami and sweet [ 10 ]. Therefore, within a moderate range, a low content of flavonoids and other phenolic compounds and a high content of free amino acids in tea tender shoots are the material basis for making high-quality tea [ 14 ]. According to the results of the biochemical components analysis and total metabolic spectrum, GC-40 was found to still have the material basis for making high-quality tea because the contents of flavonoids and free amino acids were upregulated.…”
Section: Resultsmentioning
confidence: 99%
“…The quality-related metabolites in the tender shoots of tea plants mainly include catechins, flavonoids and their glycosides, amino acids, alkaloids, nucleotides, saccharides, and organic acids [ 12 , 13 ]. Catechins, flavonoids and their glycosides, and alkaloids are mainly bitter and astringent, while amino acids, nucleotides, and saccharides are mainly umami and sweet [ 14 ]. If the content of metabolites with umami and sweet tastes in the tender shoots is high and the content of metabolites with bitter and astringent tastes is low, higher-quality tea products can be made with these raw materials [ 8 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Southern Fujian’s Oolong tea is mainly Tieguanyin, Northern Fujian’s Oolong tea is mainly Wuyi rock tea, and Guangdong’s Oolong tea is mainly Fenghuang Dancong tea [ 3 ]. Previous studies on the quality characteristics of Oolong tea from these three producing areas found that each had its own characteristics, but there was no quantitative evaluation of taste [ 6 , 23 ]. In this study, the quantitative taste evaluation was carried out to further clarify the taste differences of Oolong tea in the three production areas.…”
Section: Resultsmentioning
confidence: 99%
“…[ 5 ]. The flavor formation of Oolong tea is affected by the variety, producing areas, processing technology, season, and picking method [ 6 ]. For example, different Oolong tea cultivars have different “cultivar fragrances” [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…OPLS‐DA provides a supervised classification that can be used to distinguish between different sample species and extract differential information 27 . To investigate the differences in the volatile components among the three types of Hehong tea and distinguish them, OPLS‐DA modelling analysis was conducted on all detected compounds, and we found that the model effectively divided the three types of Hehong tea (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%